2009
DOI: 10.1055/s-0029-1215133
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided versus conventional transmural drainage for pancreatic pseudocysts: a prospective randomized trial

Abstract: We found that EUD and CTD can both be considered first-line methods of endoscopic transmural drainage of bulging pseudocysts, whereas EUD should be preferred for nonbulging pseudocysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(193 citation statements)
references
References 19 publications
3
180
0
10
Order By: Relevance
“…18 This technique showed higher technical success rate compared to conventional method in previous reports. 4,19 The present study investigated retrospectively the technical and clinical success, complication, and recurrence, in 47 patients undergoing single-step EUS-guided transmural drainage of pancreatic pseudocysts in a single center. The median follow-up time was 16.5 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 This technique showed higher technical success rate compared to conventional method in previous reports. 4,19 The present study investigated retrospectively the technical and clinical success, complication, and recurrence, in 47 patients undergoing single-step EUS-guided transmural drainage of pancreatic pseudocysts in a single center. The median follow-up time was 16.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…3 Blind endoscopic drainage carries a risk of bleeding or perforation and is not preferred for nonbulging pseudocyst because avoiding major vessels and adjacent structures is difficult. 4 After the development of endoscopic ultrasound (EUS), beside accurate diagnosis, 5 two-step EUS-guided drainage has been tried for added safety, which is performed with a duodenoscope after marking an optimal site by EUS. However, this technique prolongs the procedure time and increases patient discomfort and the need for sedation.…”
Section: Introductionmentioning
confidence: 99%
“…Our team [64] and others [72] have demonstrated that EUS-guided drainage and conventional transmural drainage techniques have fairly comparable rates of success and similar rates of complications if non bulging collection and patient at higher risk of bleeding are selectively drained using EGPD.…”
Section: Pancreatic Stonesmentioning
confidence: 91%
“…Volmar et al [46] reported that for lesions <3 cm, the EUS-guided FNA had higher accuracy than US or CT. With CT or EUS guidance, samples of the cystic fluid and cyst walls can be taken by fine needle aspiration and brushing for cytology and measurement of tumour markers, viscosity, and amylase (that will be described in the further part of this paper) [17,28,[47][48][49][50][51][52]. Similar to transabdominal US, EUS also allows a therapeutic approach such as EUS-guided pancreatic pseudocyst drainage (that will be discussed in a chapter regarding management) [53][54][55][56][57][58][59][60][61].…”
Section: Endoscopic Ultrasnonography (Eus)mentioning
confidence: 99%
“…Endoscopic drainage may be performed under EUS and endoscopy guidance. Park et al [56] compared endoscopic ultrasound (EUS)-guided transmural drainage versus conventional transmural drainage by endoscopy. Authors concluded that both EUS-guided and conventional methods could be considered first-line methods of endoscopic transmural drainage of bulging pseudocysts whereas EUS-guided assess should be preferred for non-bulging pseudocysts.…”
Section: Percutaneous and Endoscopic Drainage Of Pancreatic Pseudocystsmentioning
confidence: 99%